2020
DOI: 10.1371/journal.pone.0240025
|View full text |Cite
|
Sign up to set email alerts
|

PLA2R antibody, PLA2R rs4664308 polymorphism and PLA2R mRNA levels in Tunisian patients with primary membranous nephritis

Abstract: Background Primary membranous nephritis (PMN) is an autoimmune disease induced by the deposit of antibodies (Ab) to the phospholipase receptor A2 receptor (PLA2R) on podocytes. In this context, we aimed to assess the relationships between anti-PLA2R Ab, PLA2R rs4664308 SNP, PLA2R mRNA levels and PMN susceptibility and outcome. Methods Sixty-eight PMN patients, 30 systemic lupus erythematosus (SLE) patients with secondary MN and 30 healthy control subjects served for anti-PLA2R Ab measurement by ELISA and PLA2R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…In an Indian cohort of 114 PMN patients, rs2187668 of HLA-DQA1 was a risk factor of serum aPLA2R-Ab [ 65 ]. The risk allele of PLA2R rs4664308 in PMN development was also reported by others [ 66 ]. Both PLA2R rs4664308 and HLA-DQA1 rs2187668 SNPs are intronic [ 64 ]; their impact might be on gene expression.…”
Section: Mechanisms Underlying Pla2r- and Thsd7a-contributed Mn Pathogenesissupporting
confidence: 77%
“…In an Indian cohort of 114 PMN patients, rs2187668 of HLA-DQA1 was a risk factor of serum aPLA2R-Ab [ 65 ]. The risk allele of PLA2R rs4664308 in PMN development was also reported by others [ 66 ]. Both PLA2R rs4664308 and HLA-DQA1 rs2187668 SNPs are intronic [ 64 ]; their impact might be on gene expression.…”
Section: Mechanisms Underlying Pla2r- and Thsd7a-contributed Mn Pathogenesissupporting
confidence: 77%
“…Overall, 27 studies with a total of 5353 PMN cases and 10,777 controls were included in the present study. 13 – 35 The characteristics of included studies are summarized in Table 1 . Genotyping data of cases and controls are depicted in Supplemental Tables S1–S10 .…”
Section: Resultsmentioning
confidence: 99%
“…Biological features of included studies patients are illustrated in Supplemental Table S11 . Eighteen studies were included for the rs4664308 SNP, 13 17 , 20 , 22 , 23 , 25 , 27 , 28 , 30 , 32 34 13 for the rs3749117 SNP, 16 , 18 , 22 , 23 , 25 27 , 30 , 33 10 for the rs3749119 SNP, 13 , 18 , 20 , 25 , 29 33 16 for the rs35771982 SNP, 16 , 18 23 , 25 , 26 , 29 31 , 33 , 35 12 for the rs3828323 SNP, 13 , 18 , 19 , 25 …”
Section: Resultsmentioning
confidence: 99%
“…In children with MN, PLA 2 R-associated MN appears to be common. PLA 2 R antibody levels are closely associated with disease activity, whereas PLA 2 R antibody-negative patients often have a good prognosis[ 4 ]. MCD in children is common in male preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…To date, phospholipase A 2 receptors (PLA 2 Rs) on podocytes have been considered to be the primary antigen, and the rate of PLA 2 R positivity in the renal tissue of children with IMN is nearly 32%[ 3 ]. Circulating autoantibodies to PLA 2 R have been confirmed in approximately 80% of adults with IMN and are seldom detected in secondary MN[ 4 ]. Some studies have indicated that the titer of anti-PLA 2 R antibodies reflects disease activity and urinary protein levels.…”
Section: Introductionmentioning
confidence: 99%